(+4) + (-2) = +2

Positive 4 and Negative 2 have 4 and owes 2 which is now 2+

Standard Form: 4 - 2 = 2

Making Zero Pairs:

-16 = +16

-5 = +5

+6 = -6

-2 = +2

-10 = +10

+3 = -3

+11 = -11

-9 = +9

Chapter 2 Multiplying Intergers

Sign Rule (Negative signs)

Even = When you have an even number of NEGATIVE factors, the product is POSITIVE

Odd = When you have an odd number of NEGATIVE factors the product is NEGATIVE

(+2) x (+3) = +6

Standard form

(2) x (3) = 6

2(3) = 6

o

o ooo ooo = 6

(+2) x (+3) = 6

or

2 groups of (+3) = 6

o

o ooo ooo = -6

(+2) x (-3) = -6 ← remove 2 groups of (+3) ← use zero pairs -remove all

or

2 groups of (-3) = -6

o ooo ooo

o

(-2) x (-3)

↑ remove 2 groups of (-3) = +6

o oooo oooo oooo

o

(-3) x (-4) = +12

o

o oooooooo

(+2) x (+4) = +8

(+5) x (-2) = -10 (-4) x (+2) = -8 ← 4 x 2 for zero pairs ← remove (+) left with (-)

(-6) x (-1) = 6

Chapter 3 Dividing Integers

Sign Rule

If you have no NEGATIVE or an even number of NEGATIVE signs in a division question, the quotient is POSITIVE. When you have an odd number of NEGATIVE signs in a division question the quotient is NEGATIVE.

2 Types of Division:

Partitive Division or making parts

Partitive Division is making parts.

6 ÷ 2 = 3, how many groups of 2 are in 6?

oo|oo|oo ← There are 3 groups of 2 in 6

6 ÷ 2 = 3 and -6 ÷ (-2) = 3

3 groups of 2 ←↓

***→2→ →2→ →2→

←2-----------------------6→

3 groups of 2←↓

*****←2← ←2← ←2←

←(-6)-----------------------(-2)→

Quotative Division or sharing your total with groups

Quotative Division is sharing your total with groups.

-6 ÷ 3 = -2, share 6 with 3 groups

oooooo ← 6 totals

( ) ( ) ( ) ← 3 groups

(oo) (oo) (oo) ← 2 out of 6 totals are in 1 group

Chapter 4 Order of Operations with Integers

BEDMAS

Brackets

Exponents

Division

Multiplication

Addition

Subtraction

Steps:

1) Brackets (if there's a square bracket, always do that first then the round bracket)

2) Multiply and divide in order, left to right.

3) Add and subtract in order, left to right.

(+5) x (-3) + (-6) ÷ (+3) = ?

(+5) x (-3) + (-2) = -17

(-15) + (-2) = -17

(+5) x (-3) = -15

(-6) ÷ (+3) = -2

(-15) + (-2) = -17

= -17

## No comments:

## Post a Comment